Pengukuran Beban Kerja Operator Menggunakan Metode 10 Denyut di PT. Wirataco - Gaustama Putra; Jefri Zikrullah (Jurnal Serambi Engineering, 2022)
PT. WIRATACO is an industry with experience in road construction and construction located in the village of Keude Linteung, Seunagan Team, Nagan Raya Regency, Aceh Province. At PT.WIRACO there is a target that must be achieved so that every operator on the creaser machine works harder. However, the high demand by consumers is not fully resolved. thus causing the operator to feel tired and at least a sense of anticipation of an accident at work. the work risk that occurs in the work operator is high with work accidents that may occur. Factors that can also be caused by the workload is a hot work environment. Based on these problems, it is necessary to do research on the physical workload of each operator by applying the 10 pulse method. This research was conducted directly without the influence of other parties. From the results From the results of research conducted on 9 creaser machine operators, it can be said that 3 operators with a heavy work percentage (11.97-25.16%) and 6 operators with a light workload percentage (32.41-39.78%.) and can lock that 6 operators do not need repairs and 3 operators need repairs. Improvements given are additional rest time for operators who experience excessive workloads, the company can also provide work motivation to operators through giving gifts every month or can provide work motivation directly.